A Review Article on Health benefits of Yoga With special reference to Suryanamaskara - Rajendra , Prasad M L (International Research Journal of Ayurveda & Yoga, 2021)
In today‘s life various type of disease takes place, most of the things takes place due to lack of physical activity, mental stress, depression, unbalanced food, & other reasons. Many people who practice yoga do so to maintain their health and well-being, improve physical fitness, relieve stress, and enhance quality of life. In this article I have tried to explain the technique of practicing and health benefits of Suryanamaskara to people who practice it regularly in proper way.